Contemporary Islamic Divorce Law Reform: Dialectics Between Classical Fiqh Authority, Maqasid Al-Shari'a, And Gender Justice - Althaf Muhammad Farras Zafri; Hidayatullah Ismail (Tafáqquh: Jurnal Penelitian Dan Kajian Keislaman, 2026)
This study analyzes contemporary Islamic divorce law reform through a dialectical perspective encompassing three competing forces: the normative authority of classical fiqh across the four major legal schools (Hanafi, Maliki, Shafi'i, Hanbali), the methodological framework of maqasid al-shari'a, and the imperatives of gender justice. Employing a normative-legal method with a comparative-analytical approach, the study examines primary fiqh sources, statutory family law, and contemporary academic literature across four Muslim-majority jurisdictions — Indonesia, Egypt, Malaysia, and Morocco — as representative models of diverse reform trajectories. The findings demonstrate: (1) the classical talaq construction assigns divorce prerogatives asymmetrically to the husband, a position that was historically coherent yet now generates structural injustice; (2) maqasid al-shari'a — particularly the principles of hifz al-nafs, hifz al-nasl, and hifz al-mal — furnishes valid epistemological justification for reform; and (3) Morocco's Mudawwana 2004 constitutes the most comprehensive reform model, successfully reconciling fiqh legitimacy with gender justice. This study concludes that reforms which endure are those rooted in internal Islamic argumentation rather than external frameworks. For Indonesia, the implication is the urgent need to strengthen women's divorce rights within the Compilation of Islamic Law through maqasid-based ijtihad.